Ideals of one-branch singularities of curves of the type $W$ - Skuratovskii, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish necessary and sufficient conditions for a one-branch singularity of the type $W$ of a plane algebraic curve to have at most two-parameter families of ideals.